(untitled) (Communication & Society, 2011)
The current article shows that a large extent of the radio advertising of products related to health infringe the current legislation. The analysis of a sample of 430 different commercials, 1,664 taking into account their broadcasting frequency, has permitted to identify the four categories of product which gather the illicit claims: food, beverage, beauty and hygiene and health. The proportion of deceptions for every illicit radio spots reaches 3.99 in the generalist radio and 2.2 in the thematic radio. The most frequent type of deceit refers to products which supposedly provide a sure relief or certain cures.